RFID : - Hunt, V. Daniel (Wiley-Interscience, 2007)
This book provides an introduction to RFID technology. It describes and addresses the following: How RFID works, how it is and can be used in current and future applications. The History of RFID technology, the current state of practice and where RFID is expected to be taken in the future. The role of middleware software to route data between the RFID network and the information technology systems within an organization. Commercial and government use of RFID technology with an emphasis on a wide range of applications including retail and consumer packaging, transportation and distribution of products, industrial and manufacturing operations, security and access control. Industry standards and the regulatory compliance environment and finally, the privacy issues faced by the public and industry regarding the deployment of RFID technology.